The Economic Burden of Infective Endocarditis due to Injection Drug Use in Australia: A Single Centre Study—University Hospital Geelong, Barwon Health, Victoria - Ohide Otome; Alexander Wright; Vanika Gunjaca; Steve Bowe; Eugene Athan (Interdisciplinary Perspectives on Infectious Diseases)
Background. Injection drug use (IDU) is a well-recognized risk factor for infective endocarditis (IE). Associated complications from IDU result in significant morbidity and mortality with substantial cost implications. The aim of this study was to determine the cost burden associated with the management of IE due to IDU (IE-IDU). Methods. We used data collected prospectively on patients with a diagnosis of IE-IDU as part of the international collaboration on endocarditis (ICE). The cost of medical treatment was estimated based on diagnosis-related groups (DRG) and weighted inlier equivalent separation (WIES). Results. There were 23 episodes from 21 patients in 12 years (2002 to 2014). The costing was done for 22 episodes due to data missing on 1 patient. The median age was 39 years. The gender distribution was equal. Heroin (71%) and methamphetamine (33%) were the most frequently used. 74% (17/23) required intensive care unit (ICU) admission. The median ICU length of stay (LOS) was 4 days (IQR (Interquartile range); 2 to 40 days) whilst median total hospital LOS was 40 days (IQR; 1 to 119 days). Twelve patients (52%) underwent valve replacement surgery. Mortality was 13% (3/23). The total medical cost for the 22 episodes is estimated at $1,628,359 Australian dollars (AUD). The median cost per episode was a median cost of $ 61363 AUD (IQR: $2806 to $266,357 AUD). We did not account for lost productivity and collateral costs attributed to concurrent morbidity. Conclusion. Within the limitations of this small retrospective study, we report that the management of infective endocarditis caused by injection drug use can be associated with significant financial cost.